Wobble board balance assessment in subjects with chronic ankle instability - Fusco, Andrea; Giancotti, Giuseppe Francesco; Fuchs, Philip X.; Wagner, Herbert; Varalda, Carlo; Cortis, Cristina (Gait & posture, 2019)
•Wobble board may detect balance deficits in subjects with chronic ankle instability.•Subjects with chronic ankle instability have worst balance on their injured limb.•The single wobble board outcome reduces previous constraints of data interpretation.•Wobble boards can fill the gap between subjective and laboratory-based test.•Balance performance progress can be accurately monitored via wobble board. Wobble boards (WBs), commonly used to train postural control, have been recently equipped with accelerometers connected to a computer displaying real-time balance performances. However, little is known about their ability to detect balance deficits in subjects with unilateral chronic ankle instability (CAI). To determine if computerized WBs can detect balance deficits in subjects with unilateral CAI. Fifteen subjects with unilateral CAI and fifteen uninjured subjects performed one WB test and one Y Balance Test (YBT) during two separate randomized sessions. WB performance was assessed as the time (s) spent on the platform by keeping it flat at 0° during three 30-s trials for each limb. Normalized (%) reach distances values for anterior, posteromedial, posterolateral directions and composite were recorded for YBT. WB has been shown to be a reliable and accurate device for detecting balance deficits between and within subjects with unilateral CAI. The area under the curve for receiver operating characteristic was 0.80 (asymptotic significance 0.001), suggesting that WBs have the capability to accurately discriminate between injured and uninjured limbs. Computerized WBs can fill the gap caused by limitations between subjective-based clinical assessment and laboratory-based testing, especially in field-based settings, where specificity, transportability and time constraints are crucial. The results of the present study suggest that WBs may facilitate the detection of balance impairments in subjects with unilateral CAI, without complexity in its use or data interpretation.